Stereotactic body radiotherapy: an effective local treatment modality for hepatocellular carcinoma. (November 2014) - Klein, Jonathan; Korol, Renee; Lo, Simon S; Chu, William; Lock, Michael; Dorth, Jennifer A; Ellis, Rodney J; Mayr, Nina A; Huang, Zhibin; Chung, Hans T
ABSTRACT : Although liver-directed therapies such as surgery or ablation can cure hepatocellular carcinoma, few patients are eligible due to advanced disease or medical comorbidities. In advanced disease, systemic therapies have yielded only incremental survival benefits. Historically, radiotherapy for liver cancer was dismissed due to concerns over unacceptable toxicities from even moderate doses. Although implementation requires more resources than standard radiotherapy, stereotactic body radiotherapy can deliver reproducible, highly conformal ablative radiotherapy to tumors while minimizing doses to nearby critical structures. Trials of stereotactic body radiotherapy for hepatocellular carcinoma have demonstrated promising local control and survival results with low levels of toxicity in Child–Pugh class A patients. We review the published literature and make recommendations for the future of this emerging modality.